Chemical Degradation and Decolorization of Reactive Black B With an Inorganic Oxidant in Acidic Medium. Issue 40 (25th October 2022) - Qamar, Noshab; Ashfaq, Maria; Summer, Shazia; Khan, Sameera Razi; Masood, Summyia; Ali, Nida; Toheed, Javeria
Abstract: Due to the wide applications of the Reactive Black B (RB−B) in textile industries, it is largely present within the aqueous environment which is a serious environmental threat. Previous studies were unsuccessful to completely remove the color of RB−B from the contaminated environment. In this work, the decolorization of aqueous solutions with RB−B was performed by Potassium bromate. It was found to be a promising oxidizing agent for chemical degradation of organic pollutant. The decolorization and degradation of Reactive Black B by potassium bromate in an aqueous acidic medium was carried out at 591 nm spectrophotometrically at laboratory scale. The reaction was studied under pseudo order conditions having concentration of BrO3 − in excess than dye. Under constant conditions, the reaction was found to be first order with respect to both oxidant and reductant. The kinetic salt effect of added salt for the determination of reactive species in the rate‐determining step showed that the rate of reaction is directly related to the increasing concentration of salt, suggesting that two same charged species are involved in the rate‐determining step. Activation parameters were also calculated for the reaction. The highest decolorization percentage of RB−B (99 %) was obtained showing almost complete removal of color of dye from aqueous medium. The proposed degradation of RB−B with bromate was confirmed by qualitative and analytical tests (TDS, EC, UV‐Visible and FTIR spectroscopy). Abstract : This study describes the investigation on chemical degradation and decolorizarion of RB−B by potential inorganic oxidiant on focusing the reusability of waster water and profound nature of oxidant. Investigation shows good performance of potassium bromate for the remediation of RB−B polluted waste water.